2007
DOI: 10.1183/09031936.00024706
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to trichloramine and respiratory symptoms in indoor swimming pool workers

Abstract: The association between swimming pool characteristics and activities of employees and respiratory symptoms in employees was studied. Trichloramine levels were measured to evaluate relationships with pool characteristics and to estimate long-term exposure levels.Questionnaires were available from 624 pool workers and 38 swimming facilities. Chloramine levels were measured by area sampling over 2-h periods and analysed using ion chromatography. Work-related and general respiratory symptoms, and symptoms indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 14 publications
8
139
1
6
Order By: Relevance
“…In general, the levels of trichloramine found in this study (about 0.2 mg/m 3 in the 9 facilities) are relative low compared to several other studies, which have shown levels about 0.5 mg/m 3 (Dang et al 2010;Jacobs et al 2007;Thickett et al 2002). Almost all of the facilities in this study had baths are believed to generate higher trichloramine levels .…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…In general, the levels of trichloramine found in this study (about 0.2 mg/m 3 in the 9 facilities) are relative low compared to several other studies, which have shown levels about 0.5 mg/m 3 (Dang et al 2010;Jacobs et al 2007;Thickett et al 2002). Almost all of the facilities in this study had baths are believed to generate higher trichloramine levels .…”
Section: Discussioncontrasting
confidence: 40%
“…However, people frequently being in the environment often experience airway, eye or dermatological problems (WHO 2006;Nemery et al 2002). Several studies have showed that personnel, like lifeguards and pool attendants, suffer from nasal and throat symptoms, often together with eye irritation (Massin et al 1998;Demange et al 2009;Dang et al 2010;Fantuzzi et al 2010;Jacobs et al 2007). There are also studies indicating that children frequently visiting indoor swimming pools have an increased risk to develop asthma and allergy (Bernard et al 2005;Bernard et al 2006), although the opposite has also been found (Font-Ribera et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that lifeguards of both sexes exposed to trichloramine were at risk of developing acute irritantrelated eye, nose, and throat symptoms, but they were unable to show a relationship between cumulative exposure to trichloramine and bronchial responsiveness to methacholine. 25 In a more recent study from the Netherlands, Jacobs et al 26 found an elevated prevalence of respiratory symptoms in swimming pool workers compared with the Dutch general population.…”
Section: Respiratory Effects Of Chronic Chlorine Exposure In Lifeguarmentioning
confidence: 99%
“…Recently, Jacobs et al [43] . A regression analysis of the data proved that the number of users in the water was significantly associated to the trichloramine level, in such a way that an increase of 50 additional swimmers meant a 0.40 mg/m 3 rise.…”
Section: Water Chlorinationmentioning
confidence: 99%